Lola Levine and the ballet scheme - Brown, Monica, 1969- (Brown, Monica, 1969- Lola Levine, 2016)
"A new girl has joined Lola Levine's second-grade class. When they get off on the wrong foot, they are forced to spend time together ... and learn they have more in common than they thought"--